Aspirin dosage for the prevention of graft occlusion in people undergoing coronary surgery: a systematic review and meta-analysis - Fares Alahdab (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Background: Aspirin is almost always used after coronary artery bypass graft (CABG) surgery; however, it is unclear what optimal dose should be prescribed. In this systematic review, we evaluated the effects of high versus low-dose aspirin in patients after CABG. Methods: A comprehensive database search was conducted in several databases from date of inception until February 2018. There were no language restrictions. We included studies that compared different doses of aspirin in patients that had undergone CABG surgery. We included studies that evaluated patient-important outcomes (mortality, cardiovascular events, and gastrointestinal bleeding); and if not reported, we collected data on the surrogate outcome thromboxane B2 (TXB2). We collected relevant data and performed a meta-analysis. Results: We identified 5903 references, and after two levels of screening by two independent reviewers, we included three randomized controlled trials in the meta-analysis with a total number of 122 participants. Mean age of trial participants was 65.63 years, and 88.68% were male. We planned to analyze all possible clinical outcomes, including mortality, recurrence, and hospitalization. However, no clinical outcomes are reported by the literature. The surrogate biochemical outcome of serum TXB2 was the only outcome reported by the eligible studies. High-dose aspirin (162–325 mg once daily) achieved better suppression of TXB2 than low-dose aspirin (75–100 mg once daily) (mean difference [MD], 2.00ng/mL, 95% confidence interval [CI]: 0.72–3.32; participants = 122; studies = 3; I2 = 0%). Conclusions: We found no clinical trials addressing any of the clinical outcomes of interest. High-dose aspirin was superior to low-dose aspirin in suppressing platelet function, a surrogate outcome. Trials evaluating clinical and patient-important outcomes are needed to better inform medical practice and fill this gap in clinical knowledge.